Rahner and Lonergan on the commitment to St. Thomas Aquinas - Kpalap, Linus (Verbum – Analecta Neolatina, 2004)
Rahner and Lonergan bear witness to and emphasize a personal commitment to St. Thomas Aquinas. This personal commitment to St. Thomas is what counts, whether the study of St. Thomas is encouraged by ecclesiastical authority or not, whether Thomistic Studies boom or are considered out of fashion. The personal commitment to St. Thomas has its grounds in the ongoing relevance of St. Thomas thought, and this sets before us the tasks of appropriating his framework, and transposing Aquinas' framework into the self-understanding of the contemporary person as we search for answers and solutions to questions and problems of our time. And the process of transposing Aquinas' framework into the self-understanding of the contemporary person leads to developing the position of Aquinas, thereby arguing a case for what William A. Wallace calls "developmental Thomism."